Pelatihan Penelitian Tindakan Kelas berbasis Daring untuk Meningkatkan Kemampuan Guru di Kabupaten Pangkep - R., Mantasiah; Anwar, Muh.; Rivai, Andi Alamsyah; Rivai, Andi Tenri Ola (DEDIKASI, 2020)
Teachers have an essential role in preparing human resources that can compete with the global community. Therefore, teachers are always required to develop their abilities and professionalism. One way to build their ability to provide effective learning to students is to carry out classroom action research. Most of the teachers in Pangkajene and Kepulauan Regency still had a lack of understanding in carrying out classroom action research (CAR). Besides, there is a lack of knowledge about the writing of CAR reports and the production of scientific articles. The aim of this service is to provide online-based training to improve the understanding of CAR and scientific articles in Junior High School Teacher Group in Pangkajene and Islands Regency. A personal approach in the training process was carried out so that all teachers are expected to be able to compile proposals, reports, and scientific articles from the CAR report without any constraints. Lecture, discussion and mentoring methods are used in this training. From the implementation of this training, it was found that teachers got enormous benefits from attending this training. Teachers' understanding of CAR increased by 41%. In addition, the participants have also been able to compile a CAR proposal as well. This training can improve teacher competence and support teacher professionalism in providing effective learning.